Análise vocal (auditiva e acústica) nas disartrias - Carrillo, Luciane [UNIFESP] (2007)
BACKGROUND: neurological dysphonias are normally associated to dysarthrias and play an important role when determining the correct diagnosis. The acoustic analysis of the voice is important for understanding the speech motor disorders present in dysarthric patients. AIM: to describe the acoustic and auditory-perceptual characteristics of the voice of the different types of dysarthria. METHOD: 42 patients with well defined neurological diagnosis of dysarthria, 21 male and 21 female, were evaluated according to auditory-perceptual parameters and acoustic measures. All patients had their voices recorded. Auditory-perceptual voice analysis included: type of voice, resonance (balanced, hypernasal or laryngeal-pharyngeal), loudness (adequate, reduced, increased), pitch (adequate, low, high), and voice onset (isochronic, abrupt or breathy). For the acoustic analysis the following programs were used: GRAM 5.1.7. for the analysis of vocal quality and spectrographic tracing; and Vox Metria to obtain the objective measures. RESULTS: data obtained in the auditory-perceptual analysis indicate that the most present vocal quality was the harsh and breathy voice, laryngeal-pharyngeal resonance and instability on vocal onset. In the acoustic analysis the following was observed: instability in the spectrogram, absence of the upper sub harmonics, presence of noise between the harmonics and reduced maximum phonatory time. Jitter, Shimmer and Glottal to Noise Excitation Ratio were altered in all dysarthrias. CONCLUSION: the acoustic analysis, associated to the auditory- perceptual assessments, is of assistance in the clinical diagnosis of dysarthrias.